Synthesis and Reactivity of 4′-Deoxypentenosyl Disaccharides - Padungros, Panuwat (American Chemical Society, 2014)
[Image: see text] 4-Deoxypentenosides (4-DPs) are versatile synthons for rare or higher-order pyranosides, and they provide an entry for structural diversification at the C5 position. Previous studies have shown that 4-DPs undergo stereocontrolled DMDO oxidation; subsequent epoxide ring-openings with various nucleophiles can proceed with both anti or syn selectivity. Here, we report the synthesis of α- and β-linked 4′-deoxypentenosyl (4′-DP) disaccharides, and we investigate their post-glycosylational C5′ additions using the DMDO oxidation/ring-opening sequence. The α-linked 4′-DP disaccharides were synthesized by coupling thiophenyl 4-DP donors with glycosyl acceptors using BSP/Tf(2)O activation, whereas β-linked 4′-DP disaccharides were generated by the decarboxylative elimination of glucuronyl disaccharides under microwave conditions. Both α- and β-linked 4′-DP disaccharides could be epoxidized with high stereoselectivity using DMDO. In some cases, the α-epoxypentenosides could be successfully converted into terminal l-iduronic acids via the syn addition of 2-furylzinc bromide. These studies support a novel approach to oligosaccharide synthesis, in which the stereochemical configuration of the terminal 4′-DP unit is established at a post-glycosylative stage.